Microbial dysbiosis in roots and rhizosphere of grapevines experiencing decline is associated with active metabolic functions - Darriaut, Romain; Marzari, Tania; Lailheugue, Vincent; Tran, Joseph; Martins, Guilherme; Marguerit, Elisa; Masneuf-Pomarède, Isabelle; Lauvergeat, Virginie (Frontiers in plant science, 2024)
When grapevine decline, characterized by a premature decrease in vigor and yield and sometimes plant death, cannot be explained by pathological or physiological diseases, one may inquire whether the microbiological status of the soil is responsible. Previous studies have shown that the composition and structure of bacterial and fungal microbial communities in inter-row soil are affected in areas displaying vine decline, compared to areas with non-declining vines within the same plot. A more comprehensive analysis was conducted in one such plot. Although soil chemical parameters could not directly explain these differences, the declining vines presented lower vigor, yield, berry quality, and petiole mineral content than those in non-declining vines. The bacterial and fungal microbiome of the root endosphere, rhizosphere, and different horizons of the bulk soil were explored through enzymatic, metabolic diversity, and metabarcoding analysis in both areas. Despite the lower microbial diversity and richness in symptomatic roots and soil, higher microbial activity and enrichment of potentially both beneficial bacteria and pathogenic fungi were found in the declining area. Path modeling analysis linked the root microbial activity to berry quality, suggesting a determinant role of root microbiome in the berry mineral content. Furthermore, certain fungal and bacterial taxa were correlated with predicted metabolic pathways and metabolic processes assessed with Eco-Plates. These results unexpectedly revealed active microbial profiles in the belowground compartments associated with stressed vines, highlighting the interest of exploring the functional microbiota of plants, and more specifically roots and rhizosphere, under stressed conditions.